2020
DOI: 10.1186/s40168-020-00881-2
|View full text |Cite
|
Sign up to set email alerts
|

The extracellular vesicle of gut microbial Paenalcaligenes hominis is a risk factor for vagus nerve-mediated cognitive impairment

Abstract: Background: In a pilot study, we found that feces transplantation from elderly individuals to mice significantly caused cognitive impairment. Paenalcaligenes hominis and Escherichia coli are increasingly detected in the feces of elderly adults and aged mice. Therefore, we isolated Paenalcaligenes hominis and Escherichia coli from the feces of elderly individuals and aged mice and examined their effects on the occurrence of age-related degenerative cognitive impairment and colonic inflammation in mice. Results:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
131
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 121 publications
(135 citation statements)
references
References 55 publications
4
131
0
Order By: Relevance
“…Kim et al reported that Escherichia coli treatment increased the NF-κB + /Iba1 + and LPS + /Iba1 + cell populations in the hippocampus and LPS levels in the blood and feces and decreased the BDNF + /NeuN + cell population and tight-junction protein expression, resulting in the occurrence of depression [29]. Lee et al also reported that oral gavage of Escherichia coli and LPS caused colitis and neuroin ammation in mice through the suppression of tight-junction proteins [38]. Koo et al showed that the inhibition of IL-1β expression by pre-treatment with an IL-1R antagonist mitigated depression [39].…”
Section: Discussionmentioning
confidence: 99%
“…Kim et al reported that Escherichia coli treatment increased the NF-κB + /Iba1 + and LPS + /Iba1 + cell populations in the hippocampus and LPS levels in the blood and feces and decreased the BDNF + /NeuN + cell population and tight-junction protein expression, resulting in the occurrence of depression [29]. Lee et al also reported that oral gavage of Escherichia coli and LPS caused colitis and neuroin ammation in mice through the suppression of tight-junction proteins [38]. Koo et al showed that the inhibition of IL-1β expression by pre-treatment with an IL-1R antagonist mitigated depression [39].…”
Section: Discussionmentioning
confidence: 99%
“…Third, to understand the effect of NK109 on the vagus nerve-mediated gut–brain signaling, we prepared the SPF mice with celiac vagotomy, as reported previously [ 20 ]. The mice were separated into vehicle-treated group in sham mice (CoV), Escherichia coli K1-treated (vEcV) and NK109-treated groups in K1-treated mice with vagotomy (vENK) vehicle-treated group in sham mice (CoV), Escherichia coli K1-treated (vEcV) and NK109-treated groups in K1-treated mice with vagotomy (vENK).…”
Section: Methodsmentioning
confidence: 99%
“…For the immunohistochemistry analysis, the mice were perfused transcardially with 4% paraformaldehyde. Hippocampi and colons were removed, post-fixed with 4% paraformaldehyde, immersed in 30% sucrose solution, frozen, and sectioned using a cryostat, as reported previously [ 20 ]. The sections were incubated with antibodies for NF-κB (1:100), CD11c (1:200), Iba1 (1:200), BDNF (1:200), IL-IR (1:200), and/or NeuN (1:200) and incubated with the Alexa Fluor 488 (1:200)- or Alexa Fluor 594 (1:200)-conjugated secondary antibody [ 6 ].…”
Section: Methodsmentioning
confidence: 99%
“…Other investigators have also demonstrated that whole gut bacteria stimulate the vagus nerve indirectly via released metabolites interacting with the enteric nervous system [ 12 , 118 ]. That bacterial MV could utilize the vagus nerve to mediate gut–brain communication was suggested by a recent study by Lee et al [ 119 ]. The investigators performed a fecal transplant from both older humans and aged mice into young mice and examined changes in dementia-related behavior and physiology.…”
Section: The Role Of Bacterial MV In Microbial Communication To Thmentioning
confidence: 99%
“…The investigators performed a fecal transplant from both older humans and aged mice into young mice and examined changes in dementia-related behavior and physiology. Lee et al [ 119 ] demonstrated that MV derived from Paenalcaligenes hominis caused cognitive deficits in the brain as well as increasing the number of activated microglia in the hippocampus [ 119 ]. Cognitive deficits significantly reduced, and the hippocampal cell populations normalized in vagotomized animals suggesting that MV interaction with the vagus nerve is at least partially responsible for the MV induced changes to the brain [ 119 ].…”
Section: The Role Of Bacterial MV In Microbial Communication To Thmentioning
confidence: 99%